2019
DOI: 10.3389/fgene.2018.00750
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Modulating Long Non-coding RNAs (LncRNAs) and Their Molecular Events in Cancer

Abstract: Cancer is a global threat of health. Cancer incidence and death is also increasing continuously because of poor understanding of diseases. Although, traditional treatments (surgery, radiotherapy, and chemotherapy) are effective against primary tumors, death rate is increasing because of metastasis development where traditional treatments have failed. Autophagy is a conserved regulatory process of eliminating proteins and damaged organelles. Numerous research revealed that autophagy has dual sword mechanisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 111 publications
0
44
0
Order By: Relevance
“…LncRNAs are considered as one of the most sensitive and speci c cancer biomarkers, which participate in the development and progression of various cancers at different levels including epigenetic, transcriptional and posttranscriptional regulation [11][12][13][14]. Moreover, accumulating studies have suggested that lncRNAs promote cancer progression and predict worse prognosis in numerous cancers via regulating autophagy [15][16][17]. Therefore, it is valuable to identify key lncRNAs closely related to autophagy and prognosis in breast cancer.…”
mentioning
confidence: 99%
“…LncRNAs are considered as one of the most sensitive and speci c cancer biomarkers, which participate in the development and progression of various cancers at different levels including epigenetic, transcriptional and posttranscriptional regulation [11][12][13][14]. Moreover, accumulating studies have suggested that lncRNAs promote cancer progression and predict worse prognosis in numerous cancers via regulating autophagy [15][16][17]. Therefore, it is valuable to identify key lncRNAs closely related to autophagy and prognosis in breast cancer.…”
mentioning
confidence: 99%
“…Long non-coding RNAs are another member of the class of non-coding RNAs that could have a crucial role in cancer pathogenesis [134]. It is thought that lncRNAs exert their modulating roles via sponging of miRNAs and proteins.…”
Section: Regulation Of Autophagy By Micrornas In Cancermentioning
confidence: 99%
“…The physiological and biological roles of autophagy-regulating lncRNAs in cancer have recently been appreciated. The expression of lncRNAs substantially affects the level of autophagy at various steps of carcinogenesis, and especially in advanced metastatic cancer [134]. It has been proposed that impaired expression of MALAT1 (metastasis associated lung adenocarcinoma transcript 1) regulates autophagy in different cancers such as RTB, HCC, glioma, and GC via modulation of miRNAs, miR-101, miR-124, miR-23b-3p, as well as miR-216b [135][136][137][138].…”
Section: Regulation Of Autophagy By Micrornas In Cancermentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are de ned as RNA transcripts longer than 200 nucleotides without or with limited protein-coding potential [16][17][18]. They can regulate gene activity through regulation of DNA and protein modi cation, protein supplement, and RNA interaction [19][20][21]. More lncRNAs are identi ed and play essential roles in biological processes, including cell growth, cell differentiation, and cell cycle control [22,23].…”
Section: Introductionmentioning
confidence: 99%